2021
DOI: 10.2147/ijgm.s274568
|View full text |Cite
|
Sign up to set email alerts
|

Review of Treatment Options for Irritable Bowel Syndrome with Constipation and Chronic Idiopathic Constipation

Abstract: Irritable bowel syndrome with constipation (IBS-C) and chronic idiopathic constipation (CIC) are two common disorders of gut–brain interaction. Affected patients often first present to their primary care providers seeking care for symptoms of constipation, abdominal pain, and bloating, which have a significant impact on their health-related quality of life. These patients often require extensive counseling and reassurance, and knowledge of reliable diagnostic criteria and treatment options is imperative to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…10,11 With its diverse pathophysiological mechanisms and presenting symptoms, there is currently no definitive treatment for IBS beyond supportive treatment and symptomatic relief. [12][13][14] Management of IBS can be classified into dietary modification, modification of gut microbiome, and pharmacotherapy aimed at altering motility, sensation, and intraluminal environment. However, current treatments may have limited long-term benefits, marginal effects on QoL, or bothersome adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 With its diverse pathophysiological mechanisms and presenting symptoms, there is currently no definitive treatment for IBS beyond supportive treatment and symptomatic relief. [12][13][14] Management of IBS can be classified into dietary modification, modification of gut microbiome, and pharmacotherapy aimed at altering motility, sensation, and intraluminal environment. However, current treatments may have limited long-term benefits, marginal effects on QoL, or bothersome adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, current treatments may have limited long-term benefits, marginal effects on QoL, or bothersome adverse effects. [14][15][16] Burgeoning studies have suggested a relationship between vitamin D deficiency and multiple disease states, including IBS. 17,18 Vitamin D has putative functions in influencing cellular mechanisms, regulating gut microbiome, and modulating immune system and inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays the currently used drugs for IBS present variable efficacy and some of them are associated with long-term side effects (Lucak et al, 2017;Patel et al, 2021). Thus, the development of new therapeutic strategies could be of great social and clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Symptom-oriented pharmacological treatment algorithms manage many patients with IBS who fail to improve their lifestyle or follow psychological interventions [12]. Notably, single-agent therapy rarely relieves the symptoms in all patients [4,[13][14][15][16][17].…”
Section: Treatment For Ibs: Lack Of Curablementioning
confidence: 99%